Pendidikan Konservasi Sebagai Upaya Menumbuhkan Keperdulian Lingkungan - Rahardyan, Atalin; Nugraheni, Nursiwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Education is an important suggestion in improving and developing human resources in a nation. conservation has the meaning of preservation, namely to preserve or maintain the carrying capacity, quality, function and ability of the natural environment in a balanced manner. Conservation education is education that provides a positive influence on behavior, attitudes and ways of thinking related to the management of natural resources and the ecosystems that exist in it. The need for conservation education is to foster an attitude of environmental care in children and adults. To form humans who are aware of the importance of preserving rivers, it is necessary to foster, direct and make someone have a soul that loves the environment. Parents as the first and main educators in the household have a very big role in shaping children's attitudes and behavior to care about the environment.